Analisis Karakteristik Wisatawan di Bukit Khayangan Kota Sungai Penuh - Muhammad Mealgie Fii; Trisna Putra (Universitas Negeri Padang, 2022)
Research on visitor characteristics to Bukit Khayangan stems from a problem that the authors found, which is unknown characteristics of visitors to Bukit Khayangan. Tourist characteristics are important because they are helpful in developing facilities and infrastructure that are adaptive to visitor needs. And this study is also based on the need of Sungai Penuh City Tourism Office in recording the characteristics of visitors to tourist objects. This type of research uses descriptive quantitative survey method. The population for this study was 15,512 people and this study sample was taken using a non-probability sampling technique with a sample size of 95 people. The tool used in this study was a structured questionnaire using the Guttman scale. Research data is processed by Microsoft Excel 2010. The analytical technique in this study is quantitative descriptive analysis. The results show that: (1) Based on demographic characteristics, the majority of guests are from 1824 years old and most of them are female, have high school education/equivalent, the majority of occupations are students. member, majority income Rp. 1,500,000 and most of their marital status remains unmarried/single. (2) Based on geographical features, guests mainly come from Sungai Penuh city area with a residence distance of 20 km from tourist attractions, most of them live in coastal areas and are located in densely populated areas. casting. (3) Based on the majority of psychological characteristics 62% of tourists are of psychological type and 38% of tourists are of attribution type. Based on the results of this study, the authors suggest to the management that the development of Bukit Khayangan should be tailored to the characteristics of visitors.